2022
DOI: 10.3390/cancers14184505
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Dynamic Immune Environment Triad in Patients with Breast Cancer: Tumour, Lymph Node, and Peripheral Blood

Abstract: During the anti-tumour response to breast cancer, the primary tumour, the peripheral blood, and the lymph nodes each play unique roles. Immunological features at each site reveal evidence of continuous immune cross-talk between them before, during and after treatment. As such, immune responses to breast cancer are found to be highly dynamic and truly systemic, integrating three distinct immune sites, complex cell-migration highways, as well as the temporal dimension of disease progression and treatment. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 158 publications
0
10
0
Order By: Relevance
“…Such spatial characterization could also be extent to lymph nodes, given their increasingly importance in the context of breast cancer. 37 Our study has also clinical implications. Although anti-PD1 blockade prolongs the survival of TNBC patients, 38,39 a significant proportion of them does not benefit from immunotherapy.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Such spatial characterization could also be extent to lymph nodes, given their increasingly importance in the context of breast cancer. 37 Our study has also clinical implications. Although anti-PD1 blockade prolongs the survival of TNBC patients, 38,39 a significant proportion of them does not benefit from immunotherapy.…”
Section: Discussionmentioning
confidence: 70%
“…Considering the proven clinical importance of stromal TILs, 36 it may be envisaged that both compartments should be analyzed in order to understand the immune‐system of our patients. Such spatial characterization could also be extent to lymph nodes, given their increasingly importance in the context of breast cancer 37 …”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that some chemotherapeutic drugs appeared more effective in immuno-competent hosts than in immuno-deficient counterparts ( 20 ). These data suggested the fundamental role of global immune macroenvironment ( 17 , 24 , 25 ) as the basis for various therapies. Immunity is coordinated across diverse cell types and tissues.…”
Section: Introductionmentioning
confidence: 93%
“…23 In cancer, the antitumor responses become dysregulated and inefficient in the lymph nodes which serve as a primary site for antigen presentation and T-cell stimulation. 28 Hence, this study aims to explore the immune checkpoint molecule status and exhaustion-related facets of the CD8 + T cells found in the circulation and in the lymph nodes. Here, a subpopulation of CXCR5 + PD-1 + cytotoxic T cells was identified with high TIM-3, ICOS, and CD45RO expression in the lymph nodes from breast cancer patients but showed limited association with the clinical features of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, the antitumor responses become dysregulated and inefficient in the lymph nodes which serve as a primary site for antigen presentation and T‐cell stimulation 28 . Hence, this study aims to explore the immune checkpoint molecule status and exhaustion‐related facets of the CD8 + T cells found in the circulation and in the lymph nodes.…”
Section: Introductionmentioning
confidence: 99%